Efektivitas Undang-Undang Perlindungan Anak terhadap Pencegahan Perundungan Anak di Indonesia dan Malaysia - Miranti Puspita Sari; Syaddan Dintara Lubis (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This study aims to analyze the effectiveness of child protection laws in preventing bullying among children in Indonesia and Malaysia, examine the implementation of the applicable regulations, and identify the factors influencing the effectiveness of bullying prevention from the perspectives of criminal law and Islamic criminal law. This research is a library study employing a qualitative approach and a normative legal research method. The findings indicate that both Indonesia and Malaysia have established adequate regulations to protect children from bullying. However, the effectiveness of prevention is determined not only by the substance of the law but also by factors such as law enforcement, reporting systems, supporting facilities, community participation, and legal culture. Malaysia tends to be more effective in terms of implementation through a centralized monitoring and reporting system, while Indonesia demonstrates stronger protection of children’s rights and greater application of restorative justice.